Alteration of the gut microbial composition of critically endangered Malayan tigers (Panthera tigris jacksoni) in captivity during enrichment phase - Khairulmunir, Mohamad; Millawati, Gani; Mohd Ridwan, Abd Rahman; Kayal Vizi, Karuppannan; Abdul Latiff, Muhammad Abu Bakar; Badrul Munir, Md Zain (Springer Nature, 2024)
Enrichment activities may influence the microbiomes of captive tigers’, affecting their health, digestion, and behavior. Currently, there are few studies that address the impact of enrichment activity on tigers’ health. This study aimed to determine the diversity of the gut microbiome in captive Malayan tigers at Zoo Melaka and Night Safari during the environmental enrichment phase using a metabarcoding approach.This study utilized different enrichment activities which catered for food, sensory, and cognitive enrichment. Eleven fresh fecal samples from captive Malayan tigers at Zoo Melaka and Night Safari were collected under different conditions. All samples were extracted and 16S rRNA V3–V4 region amplicon sequencing was used to characterize the gut microbiome of captive Malayan tigers subjected to various enrichment activities. Firmicutes, Actinobacteriota, and Fusobacteriota were the dominant phyla observed in the gut microbiome of captive Malayan tigers during enrichment activities. This study revealed β-diversity significantly varied between normal and enrichment phase, however no significant differences were observed in α-diversity. This study demonstrates that environmental enrichment improves the gut microbiome of Malayan tigers because gut microbes such as Lachnoclostridium, which has anti-inflammatory effects and helps maintain homeostasis, and Romboutsia, which has a probiotic effect on the gut microbiome. Conclusions This study provides valuable insights into the effects of enrichment activities on the gut microbiome of captive Malayan tigers, offering guidance for enhancing captive management practices aimed at promoting the health and well-being of Malayan tiger in captivity.